Parental Socio-Economic Status and Students’ Engagement in Child Labour: Implication for Counselling - Musa, Titilayo (Advances in Social Sciences Research Journal, 2016)
This study examines the Parental Socio-Economic Status on Students’ Engagement in Child Labour. A structured questionnaire was designed and administered participants using simple random sampling techniques. 200 questionnaire were distributed and the data collected was analyse using correlation, regression and analysis of Variance (ANOVA) at 0.05 level The result of the findings showed that there is a significant effect of parental socio-economic status on child labour practice. Also, findings also indicated that there is no significant effect of parental income status on child labour practice. In addition, the result also showed that there is no significant effect of parental education on child labour practice. Not only has that, findings also indicated that there is no significant effect of parental occupation on child labour practice. Consequently, the findings of this study indicated that there is a significant relationship between child labour practice and student’s achievement. Based on the above, it is thus recommended that the economic situation of the country needs to be revamped so as to enhance the standard of living of the citizenry. Not only that, law should be enacted mandating all school-age children not to be found hawking during school hours. More so, Federal Government should, as a matter of urgency, ensure that the child right law is made operational and effective in all states of the federation, while attempts should be made to redistribute the national wealth such that a greater percentage is directed at taking care of citizen’s welfare. Also, Governmental and non-governmental organizations should also endeavour to create care centres for the children of the destitute and the less privileged and Government and corporate bodies should create more jobs which will alleviate poverty, and the National Assembly must ensure that a social security bill is passed into law.